2011
DOI: 10.1093/jxb/err004
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of cytokinin biosynthesis and degradation

Abstract: Cytokinin hormones are important regulators of development and environmental responses of plants that execute their action via the molecular machinery of signal perception and transduction. The limiting step of the whole process is the availability of the hormone in suitable concentrations in the right place and at the right time to interact with the specific receptor. Hence, the hormone concentrations in individual tissues, cells, and organelles must be properly maintained by biosynthetic and metabolic enzyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
283
0
10

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 351 publications
(316 citation statements)
references
References 184 publications
9
283
0
10
Order By: Relevance
“…Decomposition of tRNA was thus originaly thought to be a source of free CKs. Although, this has been considered to be insufficient to establish the significant amount of CKs required by seed plants (Barnes et al 1980), multiplication of genes coding for tRNA-IPT in basal land plants (see Frébort et al 2011) seems to be the first evolutionary step to increase the source of free CKs as described later.…”
Section: Cks As a Part Of The Trna Of Phylogenetically Distinct Organmentioning
confidence: 99%
See 4 more Smart Citations
“…Decomposition of tRNA was thus originaly thought to be a source of free CKs. Although, this has been considered to be insufficient to establish the significant amount of CKs required by seed plants (Barnes et al 1980), multiplication of genes coding for tRNA-IPT in basal land plants (see Frébort et al 2011) seems to be the first evolutionary step to increase the source of free CKs as described later.…”
Section: Cks As a Part Of The Trna Of Phylogenetically Distinct Organmentioning
confidence: 99%
“…HGT (combined with gene duplication) played a role in the evolution of Rubisco (Delwiche and Palmer 1996), the key enzyme employed by green plants. Recent genome-wide studies identified CK-related genes coding for the key enzymes of CK biosynthesis (isopentenyltransferase, IPT) and degradation (CK oxidase-dehydrogenase, CKX), respectively, in cyanobacteria and other bacteria (Frébort et al 2011). Although the function of cyanobacterial IPT and CKX in CK metabolism has not been confirmed yet (Frébort et al 2011), CKs were identified in several cyanobacteria species such as Synechocystis, Chroococcidiopsis, Anabaena, Phormidium and Oscillatoria (Hussain et al 2010).…”
Section: Ck-related Genes Originate From Bacteriamentioning
confidence: 99%
See 3 more Smart Citations